2022
DOI: 10.1007/s10680-022-09640-5
|View full text |Cite
|
Sign up to set email alerts
|

Wealth in Couples: Introduction to the Special Issue

Abstract: The assumption that economic resources are equally shared within households has been found to be untenable for income but is still often upheld for wealth. In this introduction to the special issue “Wealth in Couples”, we argue that within-household inequality in wealth is a pertinent and under-researched area that is ripe for development. To this end, we outline the relevance of wealth for demographic research, making the distinction between individual and household wealth. Drawing on a life-course perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 94 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…We also found a dependent relation (p < 0.001) between marital status and self-medication with OTCs and between employment status and self-medication with OTCs. Several studies conducted in high-income countries have concluded that marriage is positively related to high income, and those with a higher income have a greater tendency to use OTC medications [24,25]. For example, a clinical study conducted in Denmark showed that individuals with a low income tend to use prescribed medication more, whereas those with a high income tend to use more OTC medications [26].…”
Section: Discussionmentioning
confidence: 99%
“…We also found a dependent relation (p < 0.001) between marital status and self-medication with OTCs and between employment status and self-medication with OTCs. Several studies conducted in high-income countries have concluded that marriage is positively related to high income, and those with a higher income have a greater tendency to use OTC medications [24,25]. For example, a clinical study conducted in Denmark showed that individuals with a low income tend to use prescribed medication more, whereas those with a high income tend to use more OTC medications [26].…”
Section: Discussionmentioning
confidence: 99%
“…There are lacunae in the allocation of incomes to individuals (for example, wages are allocated, but capital income usually is not). In many regular surveys the ownership of savings, wealth and debt within households is often unclear -although some (though not all) assets may be capable of allocation to individuals, and there are some surveys which do measure individual wealth (cited in Lersch et al, 2022). INTRODUCTION Surveys of consumption tend to suffer the same limitation as surveys of income and, if anything, in addition to being less common, data collection on consumption may be even less individualised than collection of income data (Doss, 2021b;Guio and Van den Bosch, 2019).…”
Section: Measurement and Datamentioning
confidence: 99%
“…While the simple version of the household unitary model, i.e., the idea that household members maximize a joint utility function, is outdated for what concerns pooling and sharing of economic resources (Lersch, Struffolino & Vitali, 2022), it is still useful to explain partners' decisions regarding their level of supply and consumption (Lundberg, 1981): a situation of sustained earning losses may trigger one family member to increase their labor supply-the Added Worker Effect (henceforth: AWE; Woytinsky, 1942;Lundberg, 1985). Consequently, the deteriorating employment prospects of one partner could lead to the increase or activation of labor market participation, adding a new influx of people into the labor force.…”
Section: Introductionmentioning
confidence: 99%